2015
DOI: 10.1108/jkm-03-2015-0108
|View full text |Cite
|
Sign up to set email alerts
|

Human resource development programs for knowledge transfer and creation: the case of the Toyota Technical Development Corporation

Abstract: Purpose -The purpose of this study was to examine how human resource development (HRD) programs promote the linkage between knowledge transfer and knowledge creation in engineering departments. Design/methodology/approach -This study adopted a case study approach to the Toyota Technical Development Corporation (TTDC), an affiliated company of Toyota Motor Corporation. Data were collected from interviews with managers of the TTDC as well as its internal documents. Findings -Three major findings can be extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
14
0
6
Order By: Relevance
“…Managers' behaviours and actions, and dissatisfaction could affect intentions to quit and are reciprocated by employee development perceptions [53]. A reason new employees leave the organization is that managers do not allow employees to participate in challenging tasks [59]. Organizational managers positively influence the organizational commitment, work environment, workload were critical to an employee's intent to turnover [60].…”
Section: What Makes Employee Turnover?mentioning
confidence: 99%
“…Managers' behaviours and actions, and dissatisfaction could affect intentions to quit and are reciprocated by employee development perceptions [53]. A reason new employees leave the organization is that managers do not allow employees to participate in challenging tasks [59]. Organizational managers positively influence the organizational commitment, work environment, workload were critical to an employee's intent to turnover [60].…”
Section: What Makes Employee Turnover?mentioning
confidence: 99%
“…Explicit knowledge includes knowledge that can be transmitted through a systematic language (Nonaka and Takeuchi 1995). Matsuo (2015) states that most declarative knowledge is explicit.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The key elements in this idea are embedded in the expression 'we know more than we can tell' (Polanyi 1966;Teece 1998). Matsuo (2015) indicates that some parts of procedural knowledge are tacit. For Okumus (2013), tacit knowledge is generally informal, intuitive, and based on personal experiences.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another virtue of IM is to stimulate organizational learning (McCall et al, 1988), notably in terms of in-firm knowledge transfer (Argote and Ingram, 2000;Notais, 2009). Combining "on-the-job" and "off-the-job" training is a mean of promoting the transfer of tacit and explicit knowledge (Matsuo, 2015). Faegri et al (2010) showed that IM contributes toward improving knowledge redundancy and stimulating innovation derived from different areas of knowledge.…”
Section: Learning and Internal Mobility: New Insights Offered By Batesonmentioning
confidence: 99%